2022
DOI: 10.1371/journal.pone.0273362
|View full text |Cite
|
Sign up to set email alerts
|

A study of HBV infection and its risk factors in pregnant women in Zakho city, Iraq

Abstract: Background Despite vaccine and antiviral treatment availability, hepatitis B virus (HBV) continues to circulate among pregnant women in Iraq. HBV spread is due to many factors. This study evaluated HBV prevalence among pregnant women and Syrian refugees residing in Zakho city, Iraq, and identified risk factors associated with infection. Materials and methods Demographic data were collected from 2,054 pregnant women via a questionnaire assessing risk factors associated with HBV infection. Blood samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In the last decade, Türkiye has hosted more than 3.6 million Syrian refugees 127 . Although a study from Iraq reported high (11.3%) of HBsAg‐positive pregnant women among Syrian refugees, 128 the studies among Syrian refugees in Türkiye reported HBV prevalence similar to 129 or even lower 130 than indigenous population. Although large‐scale studies are lacking, there is no evidence that Syrian refugees contributed to HBV and/or HDV prevalence.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the last decade, Türkiye has hosted more than 3.6 million Syrian refugees 127 . Although a study from Iraq reported high (11.3%) of HBsAg‐positive pregnant women among Syrian refugees, 128 the studies among Syrian refugees in Türkiye reported HBV prevalence similar to 129 or even lower 130 than indigenous population. Although large‐scale studies are lacking, there is no evidence that Syrian refugees contributed to HBV and/or HDV prevalence.…”
Section: Discussionmentioning
confidence: 93%
“…In the last decade, Türkiye has hosted more than 3.6 million Syrian refugees. 127 Although a study from Iraq reported high (11.3%) of HBsAg-positive pregnant women among Syrian refugees, 128 prevalence similar to 129 or even lower 130 than indigenous population.…”
Section: Discussionmentioning
confidence: 97%
“…Repeated miscarriages have a huge impact not only on the psychological well‐being of individuals and their families but also on national health care systems and economic development. Recently, many reasons have been reported to induce spontaneous abortion, for example, fetal chromosomal abnormalities, alcohol consumption, smoking, cocaine use, fatigue, the number of pregnancies, age at primary birth and age at the last pregnancy, and some diseases including diabetes, celiac disease, autoimmune conditions, cervicitis, vaginitis, uterine congenital anomalies, uterine leiomyoma, intrauterine adhesions, HIV infection, hepatitis B virus infection, merkel cell polyomavirus infection, syphilis, and malaria (Alves & Rapp, 2023 ; Griebel et al., 2005 ; Hu et al., 2018 ; Khalid et al., 2022 ; Mazziotta et al., 2021 ). In addition, environmental risk factors such as arsenic, lead, and organic solvents exposure are associated to spontaneous abortion (Alves & Rapp, 2023 ; Griebel et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of education about the knowledge of Hepatitis B virus aids in increasing the disease. There are also high-risk factors in Duhok City, including drug users sharing contaminated needles, sexual encounters with infected people, and healthcare staff [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%